FASHION WEEK REMAJA DI KOTA BATAM - Zulfahmi Rauzi; Nanik Rachmawati; Taufiqqurrachman (LPPM STISIP Persada Bunda, 2023)
Fashion week is a week-long fashion exhibition event held in the city of Batam, in which the community, especially teenagers, are involved in a fashion exhibition and compete with each other's styles by using each other's clothes. The above social phenomenon, the Nagoya Thamrin Fashion Week event, has actually become an arena for quirky style contests, show-offs, and prestige through being fashionable for teenagers in Batam city. Of course, this is a trigger for the emergence of consumptive behavior that affects the lifestyle of teenagers in Batam city, who incidentally still have a status as students. In this study, the goal is to find out the phenomenon of youth fashion week in Batam City by looking at it from a social aspect regarding adolescent lifestyles that influence consumptive behavior so as to trigger a culture of consumerism towards adolescents in Batam City. This study uses a qualitative descriptive research method by providing an explanation and description of the object of the research phenomenon according to the incident at the location or in the field. This study used purposive sampling to select 10 informants. The purposeful sampling technique is a sampling technique with certain considerations. The results of the study found that in the lives of adolescents who tend to express self-pleasure through their interest in popular fashion trends, fashion has become their need to increase their self-confidence to appear in public. In addition, modernization changes the lifestyle of adolescents in Batam City, who tend to choose a more consumptive lifestyle that tends to prioritize pleasure through the development of fashion trends that are believed to be able to support appearance needs. With changes in modern lifestyle, Batam teenagers think that a person's status can be marked by changes in appearance through everything they use, for example in the form of branded clothes, branded pants, shoes, and others.